(untitled) (Research, Society and Development, 2023)
Objectives: Investigate whether there is any association between the levels of vitamin D in the blood and the seriousness of psoriasis or its development. Methods: The study is characterized as observational, retrospective, composed of 40 patients with psoriasis who had serum vitamin D levels, who underwent clinical care at a dermatology outpatient clinic in Passo Fundo/RS, from August 2019 to June 2021. Results: Of the 40 interviewees, 60% were female and 40% male. Phototypes II and III prevailed. Regarding family health history, 50% had a history of the disease. Regarding the duration of psoriasis, the predominant group was between 1-10 years (57.5%). The most prevalent psoriasis subtype was vulgaris (62.5%). Regarding serum vitamin D results, the lowest index was 15.2 ng ̸ mL, the highest was 42.3 ng ̸ mL and the average was 25.99 ng ̸mL. In the predominant age group, between 20-40 years, the proportion of patients with vitamin D was less than 30 ng ̸mL is 83.33%. The lower the phototype, the greater the proportion of patients with suboptimal serum vitamin D. In the group of patients with disease duration > 10 years, vitamin D levels were lower. There is no extreme difference in the effectiveness of treatments when analyzing the average, minimum and maximum serum levels of vitamin D. Conclusion: There was no relationship between serum levels of 25-hydroxyvitamin D (25OHD) and the development of psoriasis or even control – worsening of the clinical picture of disease.